Introduction to tissue engineering : applications and challenges - Birla, Ravi (Piscataway, N.J. : IEEE Press ; Hoboken, N.J. : Wiley, 2014)
"Covering a progressive medical field, Tissue Engineering describes the innovative process of regenerating human cells to restore or establish normal function in defective organs. As pioneering individuals look ahead to the possibility of generating entire organ systems, students may turn to this textbook for a comprehensive understanding and preparation for the future of regenerative medicine. This book explains chemical stimulations, the bioengineering of specific organs, and treatment plans for chronic diseases, like diabetes. It is a must-read for tissue engineering students and practitioners"--Provided by publisher.
Introduction to tissue engineering -- Cells for tissue engineering -- Biomaterials for tissue engineering -- Tissue fabrication technology -- Vascularization of artificial tissue -- Bioreactors for tissue engineering -- Tracheal tissue engineering -- Bladder tissue engineering -- Liver tissue engineering.
Includes bibliographical references and index.
Description based on online resource; title from resource home page (ebrary, viewed February 23, 2016).
Keywords: Tissue engineering; Nanotechnology; Regenerative medicine; Tissue engineering; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Tissue engineering; Tissue Engineering; Electronic books; Electronic books